1996
DOI: 10.1021/ja952706c
|View full text |Cite
|
Sign up to set email alerts
|

Complexes Derived from the Reaction of Manganese(III) Schiff Base Complexes and Hexacyanoferrate(III):  Syntheses, Multidimensional Network Structures, and Magnetic Properties

Abstract: The reaction between the [Mn(BS)(H2O)]+ monomeric and [Mn2(μ-BS)2(H2O)2]2+ dimeric cations and [Fe(CN)6]3- gave rise to cation−anion interaction via the formation of [FeC⋮NMn] bridges. Depending on the nature of the Schiff base and regardless of the stoichiometry used, either the trimeric anion [{Mn(BS)}2{Fe(CN)6}]- (BS = 3-MeOsalen, 6; 5-Clsalen, 7; 5-Brsalen, 8; salcy, 10) or the pentameric cation [{Mn(BS)}4{Fe(CN)6}]+ (BS = saltmen, 9) is formed, which has been assembled by the K+ cation or the ClO4 - ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 417 publications
(189 citation statements)
references
References 54 publications
12
176
1
Order By: Relevance
“…The two axial bonds are much longer than the basal bonds, which is caused by the Jahn-Teller effects. The bond distances subtended at the Mn atoms are comparable to those observed in similar manganese (III) complexes with Schiff bases [22][23][24]. The dihedral angle between the two benzene rings of the Schiff base ligand is 7.0(3)º.…”
Section: Crystal Structure Descriptionsupporting
confidence: 72%
“…The two axial bonds are much longer than the basal bonds, which is caused by the Jahn-Teller effects. The bond distances subtended at the Mn atoms are comparable to those observed in similar manganese (III) complexes with Schiff bases [22][23][24]. The dihedral angle between the two benzene rings of the Schiff base ligand is 7.0(3)º.…”
Section: Crystal Structure Descriptionsupporting
confidence: 72%
“…Schiff base complex have been playing an important role in the development of coordination chemistry related to catalysis and enzymatic reactions [1][2][3][4][5], magnetism and molecular architectures [6,7]. In particular salicylaldimines are useful for the synthesis of transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] indicated that this type of manganese Schiff base compounds are very favor of forming phenoxo oxygen-bridged structure. The two cyanidebridged heterometallic complexes have been characterized by IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%